Negotiating recovery from alcoholism in the context of the Canterbury earthquakes : a thesis submitted to Massey University in fulfilment of the requirements for a Master of Philosophy, Massey University, February 2014 - Williamson, Kerry J (Massey University, 2014)
This study employs narrative inquiry to document participants’ experiences in relation to maintaining sobriety while living through the Christchurch earthquakes. Eight women and one man were recruited via purposive sampling. Of the 9 participants, 4 were in stable recovery (greater than 5 years), 2 were in sustained recovery (between 1 and 5 years) and 3 were in early recovery (less than 1 year). Qualitative data was gathered using semi-structured, in-depth interviews utilising thematic analysis and incorporating an abductive logic. In the process of recovery from alcohol dependence previous life trauma, environmental conditions, uncertainty about the future and limited resources can be both barriers to recovery from alcoholism and growth opportunities after natural disaster. For some of the participants who contributed to this research, memories of early childhood abuse were recalled and symbolised by the seismic activity during the greater earthquake period. Participants in early recovery or relapsing continued to experience traumatic stress through re-victimisation or trauma re-enactment. Some participants in active addiction identified the earthquakes as both a hindrance and a help with their drinking and self-harming behaviour. For others, a sense of deep personal loss was felt when viewing the devastation of the ruined city which mirrored and reminded them of their life in active addiction. The research findings extend and complement existing theories of ambiguous loss and Post Traumatic Growth (PTG) within the context of addiction and recovery capital. This research also adds to the addiction, domestic violence and disaster literature that is currently available. Narratives of participants in short or long term recovery, suggested that ambiguous loss, and associated grief stemming from both situational and cumulative trauma, surfaced when viewing the earthquake damage. Living through the earthquakes was a time of adaptation and resourcefulness for all but for alcoholics in recovery extra resilience was needed to attend to addiction recovery within the larger picture of daily disaster coping. For all participants post traumatic growth was both an outcome and a process creating a more robust identity at individual levels, post disaster. Findings indicate that trauma can be instrumental in creating alcohol abuse and dependency and that recovery from alcoholism after natural disaster is a complex process requiring personal, community and political interventions.
Keywords: Alcoholics; Alcoholism; Rehabilitation; Canterbury Earthquake, N.Z., 2010; Christchurch Earthquake, N.Z., 2011; Psychological aspects; Christchurch; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology::Applied psychology